Confined pseudo-shocks as an energy source for the active solar corona - Srivastava A.K.; Murawski K.; Kuźma B.; Wójcik D.P.; Zaqarashvili T.V.; Stangalini M.; Musielak Z.E.; Doyle J.G.; Kayshap P.; Dwivedi B.N. (My University, 2025)
The Sun’s active corona requires an energy flux of ~103 W m−2 to compensate for radiative losses and to maintain its high temperature1. Plasma moves in the corona through magnetic loops2,3, which may be connected with the flows in and around sunspots4–6. Global energizing processes (for example, reconnection) play an important part in heating the corona7–9; however, energy and mass transport may also occur via shocks, waves or flows5,10,11. A full picture and the influence of such localized events, which significantly couple with various layers of the solar upper atmosphere, is still not clear. Using the Interface Region Imaging Spectrograph temporal image data of C ii 1,330 Å, we observed the presence of pseudo-shocks around a sunspot. Unlike shocks12, pseudo-shocks exhibit discontinuities only in the mass density. A two-fluid numerical simulation reproduces such confined pseudo-shocks with rarefied plasma regions lagging behind them. We find that these pseudo-shocks carry an energy of ~103 W m−2, which is enough to locally power the inner corona and also generate bulk flows (~10−5 kg m−2 s−1), contributing to the localized mass transport. If they are ubiquitous, such energized and bulky pseudo-shocks above active regions could provide an important contribution to the heating and mass transport in the overlying solar corona. © 2018, The Author(s), under exclusive licence to Springer Nature Limited.